Exosomal long non-coding RNAs: novel molecules in gastrointestinal cancers’ progression and diagnosis - Roshani, Mohammad; Baniebrahimi, Ghazaleh; Mousavi, Mahboubeh; Zare, Noushid; Sadeghi, Reza; Salarinia, Reza; Sheida, Amirhossein; Molavizadeh, Danial; Sadeghi, Sara; Moammer, Farzaneh; Zolfaghari, Mohammad Reza; Mirzaei, Hamed (Frontiers in Oncology, 2022)
Gastrointestinal (GI) cancers arise in the GI tract and accessory organs, including the mouth, esophagus, stomach, liver, biliary tract, pancreas, small intestine, large intestine, and rectum. GI cancers are a major cause of cancer-related morbidity and mortality worldwide. Exosomes act as mediators of cell-to-cell communication, with pleiotropic activity in the regulation of homeostasis, and can be markers for diseases. Non-coding RNAs (ncRNAs), such as long non-coding RNAs (lncRNA), can be transported by exosomes derived from tumor cells or non-tumor cells. They can be taken by recipient cells to alter their function, or remodel the tumor microenvironment. Moreover, due to their uniquely low immunogenicity and excellent stability, exosomes can be used as natural carriers for therapeutic ncRNAs in vivo. Exosomal lncRNAs have a crucial role in regulating several cancer processes, including angiogenesis, proliferation, drug resistance, metastasis, and immunomodulation. Exosomal lncRNA levels frequently alter according to the onset and progression of cancer. Exosomal lncRNAs can therefore be employed as biomarkers for the diagnosis and prognosis of cancer. Exosomal lncRNAs can also monitor the patient response to chemotherapy, while also serving as potential targets for cancer treatment. Here we discuss the role of exosomal lncRNAs in the biology and possible future treatment of GI cancer.